Stepwise uterine devascularisation and/or internal iliac artery ligation: an alternative to obstetric hysterectomy in the management of intractable postpartum haemorrhage - Kaur, Amrit P.; Manku, Harpoonam (International Journal of Research in Medical Sciences, 2022)
Background: Objectives of the study was to estimate the effectiveness and safety of stepwise uterine devascularisation and/or internal iliac artery ligation as alternative to obstetric hysterectomy in the management of uncontrollable postpartum haemorrhage. Methods: We conducted a retrospective cohort study at a university affiliated tertiary obstetric referral hospital in the year 2020-2021 at the department of obstetrics and gynaecology, government medical college, Amritsar. Stepwise uterine devascularisation and/or hypogastric artery ligation were performed in 35 of the 335 patients (10.45%) who had intractable postpartum haemorrhage after caesarean deliveries not responding to classic management. This technique entails ‘three’ successive procedures of bilateral vascular ligations performed in step-by-step fashion until bleeding stops. The steps were as follows: (1) Bilateral uterine artery ligation. (2) If bleeding did not stop, bilateral ovarian artery ligation was performed. (3) Additionally, bilateral ligation of the anterior division of internal iliac artery was done in a few cases in which bleeding failed to stop. After each procedure, assessment of bleeding was done before proceeding to the next step. Results: Of the 35 women who were primarily treated with stepwise uterine devascularisation, the success rate to preserve the uterus was 100%. None of the patients required hysterectomy. The postpartum period was uneventful. There were no complications and the survival rate was 100%. Among the patients followed up, normal menstruation and pregnancy occurred. Conclusions: Stepwise uterine devascularisation is an effective and safe alternative to hysterectomy for management of intractable postpartum haemorrhage.